A review of the genus Sasajiscymnus Vandenberg, 2004 from China (Coleoptera, Coccinellidae) - Tong, Junbo; Chen, Xiaosheng; Zhang, Xiaoning; Huo, Lizhi; Wu, Gang; Peng, Zhengqiang; Wang, Xingmin (Zootaxa, 2022)
In the present study, the taxonomy of the genus Sasajiscymnus Vandenberg, 2004 from China is revised. The number of Chinese species of Sasajiscymnus was increased from thirty-five to sixty-four. Twenty-seven species are newly described: S. fusinus sp. nov., S. acutus sp. nov., S. cultratus sp. nov., S. subulatus sp. nov., S. lishanicus sp. nov., S. striatus sp. nov., S. wuliangshan sp. nov., S. aureus sp. nov., S. longus sp. nov., S. latus sp. nov., S. obliquus sp. nov., S. niganulus sp. nov., S. maculatus sp. nov., S. variabilis sp. nov., S. flexus sp. nov., S. sagittalis sp. nov., S. robustus sp. nov., S. atypicus sp. nov., S. intricatus sp. nov., S. pseudoamplus sp. nov., S. flavostictus sp. nov., S. falcatus sp. nov., S. parallelus sp. nov., S. tumidus sp. nov., S. guniujiang sp. nov., S. applanatus sp. nov., S. cuonaicus sp. nov. Two species are newly recorded from China: S. ocelliferus (Canepari, 1997) and S. nepalicus (Miyatake, 1985). Pseudoscymnus hamatus (Yu & Pang, 1993) is transferred to Sasajiscymnus (comb. nov.). Five species groups of Chinese Sasajiscymnus are proposed for the first time: S. sylvaticus species group, S. hareja species group, S. atypicus species group, S. amplus species group and S. kurohime species group. Keys to the species groups of Sasajiscymnus, as well as to species level within each species group are provided. Furthermore, maps of the species distribution and detailed descriptions to fifty-nine species are also given.